2019
DOI: 10.3389/fonc.2019.01346
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Flora Disruption and Novel Biomarkers Associated With Nasopharyngeal Carcinoma

Abstract: Background: Nasopharyngeal carcinoma (NPC) is a malignant nasopharyngeal disease with a complicated etiology that occurs mostly in southern China. Intestinal flora imbalance is believed to be associated with a variety of organ malignancies. Current studies revealed that the destruction of intestinal flora is associated with NPC, and many studies have shown that intestinal flora can be used as a biomarker for many cancers and to predict cancer.Methods: To compare the differences in intestinal flora compositions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 137 publications
(135 reference statements)
0
9
0
Order By: Relevance
“…In addition, at the species level, Prevotella melaninogenica and Prevotella pallens were associated with oral squamous cell carcinoma (Pushalkar et al, 2012). Veillonella dispar was significantly increased in the intestinal flora of sporadic nasopharyngeal carcinoma patients (Jiang et al, 2019). Cigarette smoking may affect the health of smokers by affecting these bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, at the species level, Prevotella melaninogenica and Prevotella pallens were associated with oral squamous cell carcinoma (Pushalkar et al, 2012). Veillonella dispar was significantly increased in the intestinal flora of sporadic nasopharyngeal carcinoma patients (Jiang et al, 2019). Cigarette smoking may affect the health of smokers by affecting these bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…may benefit human bodies by preventing inflammatory bowel disease ( 39 ), obesity ( 40 ), and type II diabetes ( 41 ), among other advantages. It has also been suggested that Roseburia may be negatively correlated with the development of several tumors, such as CRC ( 6 , 42 , 43 ), cervical cancer ( 44 ), nasopharyngeal cancer ( 45 ), lung cancer ( 46 ), and multiple myeloma ( 47 ). Recently, clinical studies of lung cancer showed that patients with lung cancer with a higher abundance of Roseburia at the baseline were more likely to have GI reactions to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…After a careful evaluation of the literature reports on CRC microbiota based on their large size and consistent results, we provide evidence that R. intestinalis may be a definite protective factor and a reliable biomarker in CRC. However, for other cancers (nasopharyngeal carcinoma and cervical cancer), divergent results were found ( Jiang et al., 2019 ; Wang et al., 2019 ). It is notable that both studies displayed connections between Roseburia abundance and cancer risk, although the results were not related to the beneficial effect of Roseburia .…”
Section: Infection and Cancermentioning
confidence: 97%